Analysis of The Influence of Education, Health, and Internet User on Economic Growth With Labor Productivity as an Intervening Variable in Indonesia - Simatupang, Dewi Ratna Sari; Yola Anggia; Raina Linda Sari; Inggrita Gusti Sari Nasution (TALENTA Publisher, Universitas Sumatera Utara, 2023)
This study aims to see whether the Labor Productivity variable is ableto become an intervening variable between the Education, Health andInternet Users variable on Indonesia's Economic Growth in the 2015-2019 period. The method used is Path Analysis using the Eviewsprogram. The data used is in the form of panels consisting of 34provinces in Indonesia over a period of 5 (five) years. For modelselection using the Chow Test and Hausman Test and from the two teststhe Fixed Effect Model was selected. For the value of the EducationVariable, the average length of school data is used; the health variableuses life expectancy data and vaternet uses internet user data. Theresults of this study indicate that the Labor Productivity variable is notan intervening variable between the Education, Health, Internet variableand the Economic Growth variable as seen from the Sobel Test resultswhich have a value of less than 1.96 at ð›¼=5%. The direct effect of theEducation variable on Labor Productivity is negative and notsignificant. The direct effect of the Health variable on LaborProductivity is negative and significant. The direct effect of the Internetvariable on Labor Productivity is positive and not significant. Thedirect effect of the Education variable on Economic Growth is negativeand significant. The direct effect of the Health variable on EconomicGrowth is positive and not significant. The direct effect of Internetvariable on economic growth is positive and significant. The directeffect of the Labor Productivity variable on Economic Growth isnegative and not significant.